Austenitic stainless steel materials and hydrogen equipment
The austenitic stainless steel material addresses both hydrogen embrittlement and weather resistance by optimizing chemical composition and passive film properties, ensuring enhanced performance in hydrogen environments.
Patent Information
- Application Number
- JP2021096540
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-09
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2041-06-09
AI Technical Summary
Austenitic stainless steels used in hydrogen environments face challenges in achieving both hydrogen embrittlement resistance and weather resistance, with existing materials lacking sufficient study and improvement in weather resistance.
An austenitic stainless steel material with controlled chemical composition and passive film properties, including specific element ratios and A value, promotes deformation twinning, suppresses martensite formation, and enhances Cr oxide content in the passive film, achieved through controlled cold working and polishing processes.
The material exhibits improved hydrogen embrittlement resistance and weather resistance, suitable for high-pressure hydrogen environments, maintaining strength and elongation, and is applicable in hydrogen equipment.
Smart Images

Figure 0007618508000003 
Figure 0007618508000001 
Figure 0007618508000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an austenitic stainless steel material and hydrogen equipment. [Background technology]
[0002] In recent years, hydrogen energy has been attracting attention as a clean energy source that does not emit greenhouse gases such as carbon dioxide. In order to utilize hydrogen energy, there is a demand for the establishment of hydrogen-related technologies such as hydrogen production, storage, and transportation.
[0003] On the other hand, there are various problems in establishing hydrogen-related technologies. One of them is the problem of hydrogen embrittlement. Hydrogen energy uses hydrogen gas as a fuel source. For this reason, when metal materials are used in related devices such as hydrogen production devices and storage devices, the hydrogen gas causes the materials to become embrittled, which is known as hydrogen embrittlement.
[0004] From the viewpoints of manufacturing cost, strength, corrosion resistance, etc., austenitic stainless steel is one of the metallic materials used for the above-mentioned related devices. Therefore, in order to suppress hydrogen embrittlement, austenitic stainless steels with improved hydrogen embrittlement resistance have been developed.
[0005] For example, Patent Documents 1 and 2 disclose high-Mn austenitic stainless steels that are excellent in hydrogen embrittlement resistance at low temperatures and in cost-effectiveness. The austenitic stainless steels disclosed in Patent Documents 1 and 2 improve cost-effectiveness and hydrogen embrittlement resistance by adjusting the chemical composition to a predetermined amount. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2019-143227 A [Patent Document 2] JP 2019-143228 A Summary of the Invention [Problem to be solved by the invention]
[0007] In addition, in recent years, weather resistance has also been required for austenitic stainless steel materials used in hydrogen environments. This is because, as the use environments have become more diverse, it has become necessary to suppress deterioration in environments where material deterioration is likely to progress, such as outdoors. However, the austenitic stainless steel materials disclosed in Patent Documents 1 and 2 do not consider weather resistance at all. For this reason, there is room for improvement in the weather resistance of the above steel materials.
[0008] Thus, in austenitic stainless steel materials used as members and components of hydrogen-related equipment, it is difficult to achieve both hydrogen embrittlement resistance and weather resistance.
[0009] An object of the present invention is to solve the above problems and to provide an austenitic stainless steel material having improved resistance to hydrogen embrittlement and weather resistance. [Means for solving the problem]
[0010] The present invention has been made to solve the above problems, and the gist of the present invention is the following austenitic stainless steel material.
[0011] (1) An austenitic stainless steel material having a passive film, Chemical composition, in mass%, C: 0.20% or less, Si: 2.0% or less, Mn: 6.0-20.0%, P:0.060% or less, S: 0.0080% or less, Cr: 10.0-18.0%, Ni: 4.0-12.0%, N: 0.01 to 0.30%, Cu:4.0% or less, Mo: 3.0% or less Al: 0-0.20%, Ca: 0-0.01%, B: 0~0.01%, Mg: 0 to 0.01%, Nb: 0-1.0%, Ti: 0-1.0%, V: 0~1.0%, W: 0-2.0%, Zr: 0-1.0%, Co: 0-2.0%, Ga: 0 to 0.10%, Hf: 0~0.10%, REM: 0~0.10%, The balance is Fe and impurities. The A value calculated by the following formula (i) is 30.0 to 60.0, The austenitic stainless steel material, wherein the passive film satisfies the following formulas (ii) to (iv): A value=3.2Mn+0.7Cr+6.2Ni+38.7N+4.8Cu+9.3Mo -53 (i) I Fe / I O ≦1.0 (ii) 0.3 Cr / I O ≦2.0 (iii) I Mn / I O <0.3 (iv) Here, each element symbol in the above formula (i) represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero, and each symbol in the above formulas (ii) to (iv) represents the intensity of each element measured by glow discharge optical emission spectrometry, and is defined as follows: I Fe : Fe intensity (cps) at the depth position where the O intensity is half that of the surface O intensity I O : O intensity at half the surface O intensity (cps) I Cr : Cr intensity (cps) at the depth position where the O intensity is half that of the surface O intensity IMn : Mn intensity (cps) at the depth position where the O intensity is half that of the surface O intensity
[0012] (2) Vickers hardness is 200 to 500 HV1; In terms of crystal structure, 97% or more of the area is an fcc structure. The austenitic stainless steel material according to (1) above.
[0013] (3) The chemical composition is, in mass%, Al: 0.01 to 0.20%, Ca: 0.001-0.01%, B: 0.0002~0.01%, Mg: 0.0002~0.01%, Nb: 0.01 to 1.0%, Ti: 0.01 to 1.0%, V: 0.01 to 1.0%, W: 0.01-2.0%, Zr: 0.01-1.0%, Co: 0.01 to 2.0%, Ga: 0.01 to 0.10%, Hf: 0.01 to 0.10%, and REM: 0.01~0.10%, The austenitic stainless steel material according to the above (1) or (2), comprising one or more selected from the following:
[0014] (4) The austenitic stainless steel material according to any one of (1) to (3) above, which is used in a high-pressure hydrogen gas environment.
[0015] (5) Hydrogen equipment comprising the austenitic stainless steel material according to any one of (1) to (4) above.
[0016] (6) The hydrogen equipment according to (5) above, wherein the hydrogen equipment is a tank body, a tank nozzle, a liner, a pipe, a valve, or a heat exchanger. Effect of the Invention
[0017] According to the present invention, it is possible to obtain an austenitic stainless steel material having improved resistance to hydrogen embrittlement and weather resistance. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic diagram showing an example of the formation state of a passive film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present inventors have conducted studies to obtain an austenitic stainless steel material having improved strength in addition to hydrogen embrittlement resistance and weather resistance, and have obtained the following findings (a) to (d).
[0020] (a) In cold working during steel manufacturing, by promoting plastic deformation by twinning, high strength can be obtained by work hardening and hydrogen embrittlement resistance can be improved. In order to generate plastic deformation by twinning, it is effective to control the A value, which is an index of the state of plastic deformation in steel. This is because twinning deformation can be promoted by controlling the A value. On the other hand, excessive inclusion of elements such as Ni, N, Cu, and Mo may suppress plastic deformation by twinning. Therefore, within the range of the chemical composition of the steel, it is effective to increase the content of Mn, which is economical. Then, to control the A value.
[0021] (b) Furthermore, in the cold working during the production of the steel material, it is preferable that the generation of processing-induced martensite, which is susceptible to hydrogen embrittlement, is small, and that the steel has an austenite single-phase metal structure (face-centered cubic: fcc). This makes it possible to suppress a decrease in hydrogen embrittlement resistance. In addition, from the viewpoint of hydrogen embrittlement resistance as well as strength and weather resistance, it is preferable that the Vickers hardness is in the range of 200 to 500 HV1.
[0022] (c) As mentioned above, cold working is necessary to increase strength, but the passive film formed after cold working tends to have a higher ratio of Fe oxide and be thicker than when cold working is not performed. On the other hand, it is effective to reduce the ratio of Fe and Mn oxides and increase the ratio of Cr oxide near the interface between the passive film and the base material in order to improve weather resistance. For this reason, in order to control the oxides on the surface, it is preferable to once remove the passive film after cold working and then repassivate the passive film.
[0023] (d) In order to perform the above-mentioned repassivation, it is desirable to mechanically polish or electrolytically polish the surface of the steel material after cold working. In particular, by controlling the conditions of electrolytic polishing, it is possible to reduce the ratio of Fe and Mn oxides and increase the ratio of Cr oxides on the surface of the steel material after cold working. As a result, it is possible to improve weather resistance.
[0024] An embodiment of the present invention has been made based on the above findings. Each requirement of this embodiment will be described in detail below.
[0025] 1.Chemical composition The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."
[0026] C: 0.20% or less C is an element effective in stabilizing the austenite phase and improves hydrogen embrittlement resistance. However, excessive C content promotes grain boundary precipitation of Cr-based carbides, reducing weather resistance and hydrogen embrittlement resistance after cold working. For this reason, the C content is set to 0.20% or less. The C content is preferably set to 0.15% or less, and more preferably set to 0.10% or less. On the other hand, in order to obtain the above effect, the C content is preferably set to 0.01% or more.
[0027] Si:2.0% or less Silicon is an effective element for deoxidation, and contributes to improving hydrogen embrittlement resistance and strength through solid solution strengthening. However, excessive silicon content promotes the formation of intermetallic compounds such as σ phase, which reduces cold workability. For this reason, the silicon content is set to 2.0% or less. The silicon content is preferably set to 1.0% or less. On the other hand, in order to obtain the above effects, the silicon content is preferably set to 0.1% or more.
[0028] Mn: 6.0-20.0% Mn is an element that stabilizes the austenite phase and promotes the occurrence of deformation twins during cold working and the subsequent process, thereby contributing to the improvement of strength and hydrogen embrittlement resistance. It also increases the solid solubility limit of N, which indirectly contributes to the reduction of expensive Ni. For this reason, the Mn content is set to 6.0% or more. The Mn content is preferably set to 8.0% or more. However, excessive Mn content promotes the formation of the ε phase, which is highly susceptible to hydrogen embrittlement, and instead reduces hydrogen embrittlement resistance. For this reason, the Mn content is set to 20.0% or less. The Mn content is preferably set to 15.0% or less, and more preferably set to 10.0% or less.
[0029] P:0.060% or less P is an element contained in steel as an impurity, but it may become concentrated in the final solidification process, lower the melting point of steel, and promote solidification cracking (hot cracking). For this reason, the P content is set to 0.060% or less. From the viewpoint of improving hot cracking resistance, the P content is preferably set to 0.030% or less, and more preferably set to 0.025% or less. On the other hand, excessive reduction of P leads to an increase in manufacturing costs, so the P content is preferably set to 0.005% or more.
[0030] S: 0.0080% or less S is an element contained in steel as an impurity, and like P, it may promote solidification cracking (hot cracking). For this reason, the S content is set to 0.0080% or less. The S content is preferably set to 0.0030% or less, and more preferably set to 0.0020% or less. However, excessive reduction of S increases the manufacturing cost. For this reason, the S content is preferably set to 0.0001% or more.
[0031] Cr: 10.0~18.0% Cr is an element necessary for improving the corrosion resistance of stainless steel. Therefore, the Cr content is set to 10.0% or more. The Cr content is preferably set to 13.0% or more. From the viewpoint of weather resistance, the Cr content is preferably set to 15.0% or more. However, Cr is a ferrite forming element. Therefore, excessive Cr content destabilizes the austenite phase and reduces hydrogen embrittlement resistance. It also reduces cold workability. Therefore, the Cr content is set to 18.0% or less. The Cr content is preferably set to 17.0% or less.
[0032] Ni: 4.0-12.0% Ni, like Mn, stabilizes the austenite phase and promotes the formation of deformation twins during cold working and thereafter, thereby increasing strength and improving hydrogen embrittlement resistance. Ni also improves weather resistance. For this reason, the Ni content is set to 4.0% or more. The Ni content is preferably set to 6.0% or more, and more preferably set to 7.0% or more. However, excessive Ni content inhibits deformation twins after cold working, resulting in a decrease in strength and hydrogen embrittlement resistance. For this reason, the Ni content is set to 12.0% or less. The Ni content is preferably set to 10.0% or less, and more preferably set to 9.0% or less.
[0033] N: 0.01 to 0.30% Like Mn and Ni, N stabilizes the austenite phase and promotes the occurrence of deformation twins during cold working and the subsequent process, thereby increasing strength and improving hydrogen embrittlement resistance. It also enhances pitting corrosion resistance and weather resistance. For this reason, the N content is set to 0.01% or more. When the effects of N are to be actively utilized, the N content is preferably set to 0.10% or more. However, excessive N content may cause internal defects such as blowholes, and the hot workability, cold workability, and hydrogen embrittlement resistance are reduced. For this reason, the N content is set to 0.30% or less. The N content is preferably set to 0.25% or less.
[0034] Cu:4.0% or less Cu is an element mixed in from raw materials such as scrap, and stabilizes the austenite phase to improve hydrogen embrittlement resistance. Cu also improves weather resistance. On the other hand, excessive Cu content not only impairs manufacturability, but also inhibits the formation of deformation twins after cold working, reducing strength and hydrogen embrittlement resistance. For this reason, the Cu content is set to 4.0% or less. The Cu content is preferably set to 3.0% or less, and more preferably set to 1.5% or less. However, excessive reduction of Cu leads to restrictions on melting raw materials and increases manufacturing costs. For this reason, the Cu content is preferably set to 0.01% or more.
[0035] Mo: 3.0% or less Mo is mixed in from raw materials such as scrap, and is an element that is effective in improving hydrogen embrittlement resistance. On the other hand, excessive Mo content promotes the formation of δ-ferrite phase, reducing manufacturability. It also suppresses the formation of deformation twins after cold working, reducing strength and hydrogen embrittlement resistance. For this reason, the Mo content is set to 3.0% or less. It is preferable that the Mo content is set to 2.0% or less. However, excessive reduction of Mo leads to restrictions on the melting raw materials and increases manufacturing costs. For this reason, the Mo content is preferably set to 0.01% or more.
[0036] In addition to the above elements, one or more elements selected from Al, Ca, B, Mg, Nb, Ti, V, W, Zr, Co, Ga, Hf, and REM may be contained within the ranges shown below. The reasons for limiting each element will be explained.
[0037] Al: 0 to 0.20% In addition to being an effective deoxidizing element, Al has the effect of suppressing the grain boundary segregation of low melting point elements and strengthening the grain boundaries. As a result, manufacturability and the like are improved, and cold workability is improved. For this reason, Al may be contained as necessary. However, if Al is contained in excess, AlN is precipitated, which rather reduces manufacturability. In addition, it reduces the solubility of N, which reduces hydrogen embrittlement resistance. Therefore, the Al content is set to 0.20% or less. The Al content is preferably set to 0.08% or less. On the other hand, in order to obtain the above effects, the Al content is preferably set to 0.01% or more.
[0038] Ca: 0-0.01% Ca has the effect of suppressing the grain boundary segregation of low melting point elements and strengthening the grain boundary. As a result, manufacturability and cold workability are improved. For this reason, it may be contained as necessary. However, if Ca is contained in excess, inclusions are formed, which in turn reduces manufacturability and corrosion resistance. Therefore, the Ca content is set to 0.01% or less. On the other hand, in order to obtain the above effect, the Ca content is preferably set to 0.001% or more.
[0039] B: 0~0.01% B strengthens grain boundaries, improves strength, and improves hot workability and cold workability. Therefore, it may be contained as necessary. However, excessive B content promotes grain boundary precipitation of boron compounds (BN, BC, Cr2B), reducing workability and corrosion resistance. Therefore, the B content is set to 0.01% or less. On the other hand, in order to obtain the above effects, the B content is preferably set to 0.0002% or more.
[0040] Magnesium: 0 to 0.01% Mg is an element having a deoxidizing effect and has the effect of improving manufacturability. Therefore, it may be contained as necessary. However, if Mg is contained in excess, manufacturability decreases in refining and the like, and manufacturing costs increase. Therefore, the Mg content is set to 0.01% or less. On the other hand, in order to obtain the above effect, the Mg content is preferably 0.0002% or more, and more preferably 0.0005% or more.
[0041] Nb: 0-1.0% Nb has the effect of forming carbonitrides, refining crystal grains, and strengthening grain boundaries. As a result, it contributes to improving strength. For this reason, it may be contained as necessary. However, if Nb is contained in excess, the solid solution N concentration decreases, which leads to a decrease in hydrogen embrittlement resistance and weather resistance, as well as a decrease in hot workability and cold workability. Therefore, the Nb content is set to 1.0% or less. The Nb content is preferably set to 0.50% or less. On the other hand, in order to obtain the above effect, the Nb content is preferably set to 0.01% or more.
[0042] Ti: 0-1.0% Ti has the effect of forming carbonitrides, refining crystal grains, and strengthening grain boundaries. As a result, it has the effect of improving strength. For this reason, it may be contained as necessary. However, if Ti is contained in excess, the solid solution N concentration decreases, and hydrogen embrittlement resistance and weather resistance decrease, as well as hot workability and cold workability decrease. Therefore, the Ti content is set to 1.0% or less. The Ti content is preferably set to 0.50% or less. On the other hand, in order to obtain the above effect, the Ti content is preferably set to 0.01% or more.
[0043] V: 0 to 1.0% V has the effect of improving strength by dissolving in steel or precipitating as carbonitride. Therefore, it may be contained as necessary. However, if an excessive amount of V is contained, an excessive amount of carbonitride is formed, and hot workability and cold workability are deteriorated. Therefore, the V content is set to 1.0% or less. On the other hand, in order to obtain the above effect, the V content is preferably set to 0.01% or more.
[0044] W: 0~2.0% W has the effect of improving strength and weather resistance. Therefore, it may be contained as necessary. However, if an excessive amount of W is contained, the manufacturability and raw material cost increase, so the W content is set to 2.0% or less. On the other hand, in order to obtain the above effect, the W content is preferably set to 0.01% or more.
[0045] Zr: 0-1.0% Zr has a deoxidizing effect. It also has an effect of improving weather resistance. Therefore, it may be contained as necessary. However, if Zr is contained in excess, toughness and workability decrease. Therefore, the Zr content is set to 1.0% or less. The Zr content is preferably set to 0.50% or less. On the other hand, in order to obtain the above effects, the Zr content is preferably set to 0.01% or more.
[0046] Co: 0-2.0% Co has the effect of improving corrosion resistance and stabilizing the austenite phase. Therefore, it may be contained as necessary. However, if an excessive amount of Co is contained, the manufacturing cost increases, so the Co content is set to 2.0% or less. On the other hand, in order to obtain the above effects, the Co content is preferably set to 0.01% or more.
[0047] Ga: 0 to 0.10% Ga has the effect of improving hot workability. Therefore, it may be contained as necessary. However, if Ga is contained in excess, manufacturability decreases. Therefore, the Ga content is set to 0.10% or less. On the other hand, in order to obtain the above effect, the Ga content is preferably set to 0.01% or more.
[0048] Hf: 0~0.10% Hf has a deoxidizing effect and has the effect of improving weldability. Therefore, it may be contained as necessary. However, if an excessive amount of Hf is contained, manufacturability such as refining decreases. Therefore, the Hf content is set to 0.10% or less. On the other hand, in order to obtain the above effect, the Hf content is preferably set to 0.01% or more.
[0049] REM: 0~0.10% REM has a deoxidizing effect and is effective in improving manufacturability. It also has an effect of improving corrosion resistance. For this reason, it may be contained as necessary. However, if REM is contained in excess, not only does the effect saturate, but manufacturability such as refining decreases. For this reason, the REM content is set to 0.10% or less. On the other hand, in order to obtain the above effects, the REM content is preferably set to 0.01% or more.
[0050] REM refers to a total of 17 elements, including Sc, Y and lanthanides, and the above REM content refers to the total content of these elements. In industry, REM is often added in the form of misch metal.
[0051] In the chemical composition of this embodiment, the balance is Fe and impurities. Here, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of austenitic stainless steel materials, and are permissible within a range that does not adversely affect this embodiment.
[0052] A value In the chemical composition of this embodiment, the A value, which is an index of the stability of the austenite phase and an index of the plastic deformation mechanism, is set to 30.0 to 60.0. The A value is calculated by the following formula (i).
[0053] A value=3.2Mn+0.7Cr+6.2Ni+38.7N+4.8Cu+9.3Mo -53 (i) In the above formula (i), each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero.
[0054] If the A value is less than 30.0, the stability of the austenite phase is low and deformation-induced martensite is formed. As a result, the crystal grains that are not only face-centered cubic (fcc) but also body-centered cubic (bcc) increase, and hydrogen embrittlement resistance decreases. In addition, deformation-induced martensite with a high strain acts as a starting point for corrosion, and weather resistance decreases. For this reason, the A value is set to 30.0 or more.
[0055] However, if the A value exceeds 60.0, the occurrence of deformation twins after cold working is suppressed, leading to a decrease in strength and elongation in a high-pressure hydrogen gas environment. As a result, hydrogen embrittlement resistance decreases. In addition, raw material costs increase, leading to a decrease in manufacturability. For this reason, the A value is set to 60.0 or less. From the viewpoints of strength after cold working, hydrogen embrittlement resistance, economic efficiency, and manufacturability, the A value is preferably set to a range of 35.0 to 50.0.
[0056] 2. Passive film In the austenitic stainless steel material according to this embodiment, in order to improve weather resistance, the ratios of Fe oxide, Cr oxide, and Mn oxide in the passive film are set to the following ranges.
[0057] The passive film satisfies the following formulas (ii) to (iv). I Fe / I O ≦1.0 (ii) 0.3 Cr / I O ≦2.0 (iii) I Mn / I O <0.3 (iv) In the above formulas (ii) to (iv), each symbol represents the intensity of each element measured by glow discharge optical emission spectrometry, and is defined as follows:
[0058] I Fe : Fe intensity (cps) at the depth position where the O intensity is half that of the surface O intensity I O : O intensity at half the surface O intensity (cps) I Cr : Cr intensity (cps) at the depth position where the O intensity is half that of the surface O intensity I Mn : Mn intensity (cps) at the depth position where the O intensity is half that of the surface O intensity
[0059] Here, in the austenitic stainless steel material according to the present embodiment, it is desirable to lower the abundance ratio of Fe oxide and Mn oxide in the passive film, while increasing the abundance ratio of Cr oxide. The passive film is formed on the surface of the base material as shown in FIG. 1. In GDS, the distribution of each element is examined in the depth direction from the surface. The transition of the concentration distribution of each element is different, but for example, the O concentration decreases as it moves from the surface to the base material in the depth direction. The passive film is defined as the region up to the depth position where the intensity of O at the surface, i.e., the maximum intensity of O, is 1 / 2. In other words, the interface between the passive film and the base material (base steel sheet) is defined as the position where the intensity of O is 1 / 2 of the intensity of O at the surface.
[0060] The austenitic stainless steel material of this embodiment must satisfy the above formulas (ii) to (iv).
[0061] If the value of the left side of formula (ii) exceeds 1.0, the amount of Fe oxide in the passive film becomes excessive, and weather resistance is reduced. Therefore, the value of the left side of formula (ii) is set to 1.0 or less. Although there is no particular lower limit for the value of the left side of formula (ii), from the viewpoints of hydrogen embrittlement resistance and manufacturability, it is preferably set to 0.3, and more preferably to 0.5.
[0062] Furthermore, when the value in the formula (iii) is 0.3 or less, the ratio of Cr oxide is small, and weather resistance is reduced. On the other hand, it is difficult for the value in the formula (iii) to exceed 2.0 in the steel material having the chemical composition of this embodiment. Moreover, it becomes necessary to contain an excessive amount of Cr, which not only requires surface treatment but also leads to a decrease in hydrogen embrittlement resistance and strength. For this reason, the value in the formula (iii) is set to 2.0 or less. The value in the formula (iii) is preferably set in the range of 0.3 to 1.5, and more preferably in the range of 0.5 to 1.0.
[0063] Furthermore, if the value of the left side of formula (iv) is 0.3 or more, the amount of Mn oxide in the passive film becomes excessive, and weather resistance decreases. Therefore, the value of the left side of formula (iv) is made less than 0.3. There is no particular lower limit for the value of the left side of formula (iv), but from the viewpoints of hydrogen embrittlement resistance and manufacturability, it is preferably 0.05, and more preferably 0.1.
[0064] Here, the intensity of each of the above elements can be measured by glow discharge optical emission spectrometry (hereinafter, referred to as "GDS"). The measurement conditions of GDS are, for example, a pulse sputtering mode with an output of 20 W and a pressure of 600 Pa, and a sputtering depth of 0.1 μm. By using the pulse sputtering mode of GDS, the measurement accuracy of O, Fe, Cr, and Mn in the passive film with a thickness of 0.001 to 0.01 μm can be maintained.
[0065] 3. Vickers hardness The Vickers hardness of the austenitic stainless steel material in this embodiment becomes hard due to work hardening. Therefore, the Vickers hardness is preferably 200 to 500 HV1. If the Vickers hardness is less than 200 HV1, it is difficult to obtain a desired strength of 800 MPa or more. Therefore, the Vickers hardness is preferably 200 HV1 or more. On the other hand, if the Vickers hardness exceeds 500 HV1, the tensile strength is likely to exceed 1700 MPa, and the elongation of the material itself is greatly reduced. As a result, it is also difficult to maintain elongation in a high-pressure hydrogen gas environment.
[0066] In addition, when a processing-induced martensite phase (body-centered cubic: bcc) is generated during cold working and the subsequent plastic deformation, and the ratio of the austenite phase (face-centered cubic: fcc) decreases, this leads to a decrease in hydrogen embrittlement resistance. For this reason, the Vickers hardness is preferably 500HV1 or less. From the viewpoint of high strength and hydrogen embrittlement resistance, the Vickers hardness is more preferably in the range of 250 to 450HV1.
[0067] The Vickers hardness should be measured under the following conditions in accordance with JIS Z 2244:2020. Specifically, a cross-section of a resin-embedded sample should be prepared, and a load of 1 kg (9.8 N) should be applied at approximately t / 2, and the Vickers hardness should be measured using a Vickers hardness tester. The test force should be held for 20 seconds.
[0068] 4. Crystal structure In the austenitic stainless steel material according to the present embodiment, it is desirable to suppress the generation of deformation-induced martensite after deformation in order to suppress the deterioration of hydrogen embrittlement resistance, and therefore, it is preferable that the crystal structure has an area ratio of 97% or more of the fcc structure.
[0069] If the area ratio of crystal grains having the fcc structure is less than 97%, a large amount of δ-ferrite and processing-induced martensite having the bcc structure is generated, which is undesirable from the viewpoint of hydrogen embrittlement resistance. Therefore, it is preferable that the area ratio is 97% or more of the fcc structure. Note that, although some grains having the bcc structure, such as δ-ferrite, may be formed unavoidably, even in such a case, if the area ratio of crystal grains having the bcc structure is less than 3%, it is acceptable because it has little effect on hydrogen embrittlement resistance.
[0070] The crystal structure can be measured by the following procedure. Specifically, X-ray diffraction is performed on the measurement surface of the above-mentioned EBSP, and the area ratio of the fcc structure grains and the bcc structure grains is calculated. The conditions for X-ray diffraction are CuKα radiation, an applied voltage of 40 kv, and 2θ in the range of 30°≦2θ≦90°.
[0071] 5.Applications The austenitic stainless steel material according to this embodiment is preferably used in hydrogen equipment that requires light weight and compactness due to high strength in a high pressure hydrogen environment, such as the main body of a tank that stores hydrogen gas and liquid hydrogen, tank nozzles, liners, piping that serves as a hydrogen gas flow path, valves, heat exchangers, etc.
[0072] 6. Manufacturing method A preferred method for producing the austenitic stainless steel material according to this embodiment will be described. The austenitic stainless steel material according to this embodiment can obtain the effects described above regardless of the production method, but can be stably produced, for example, by the following production method.
[0073] In the following description, for the sake of simplicity, the shape of the steel material will be described as a steel plate, but the shape of the steel material is not particularly limited. For example, a plate-like, rod-like, or tubular shape is possible. A processing method according to each shape may be selected.
[0074] The steel adjusted to the above-mentioned chemical composition is melted and cast by a conventional method to obtain a steel slab to be subjected to hot rolling. Then, hot rolling is performed by a conventional method. The conditions during hot rolling are not particularly limited, but usually, the heating temperature of the steel slab is preferably 1050 to 1250°C, and the rolling reduction is preferably in the range of 20 to 99%. After hot rolling, annealing and pickling may be performed as necessary. The annealing temperature in this case is not particularly limited, but may be in the range of 1050 to 1100°C, for example.
[0075] Next, cold rolling and annealing are performed. The annealing immediately before the final cold rolling is called a solution treatment, and the solution treatment is also performed in the same manner. In addition, pickling is performed as necessary. Cold rolling is performed, for example, at a rolling reduction rate in the range of 20 to 90%, and the subsequent annealing is preferably performed by isothermal holding at 1000 to 1150°C for 1 to 600 seconds. Cold rolling, annealing, and pickling may be repeated multiple times in order to obtain a steel material of the final required thickness.
[0076] Solution treatment is performed immediately before the final finish cold rolling for work hardening. In the solution treatment, heat treatment is preferably performed under conditions of isothermal holding at 1000 to 1150°C for 1 to 600 seconds. If the solution treatment temperature is less than 1000°C, recrystallization is insufficient, and twin deformation is not sufficiently achieved during the finish cold rolling. For this reason, the solution treatment temperature is preferably 1000°C or higher. On the other hand, if the solution treatment temperature exceeds 1150°C, the crystal grains become coarse (more than 0.1 mm) and the strength decreases. For this reason, the solution treatment temperature is preferably 1150°C or lower.
[0077] Finally, final cold rolling is performed to obtain a work-hardened steel material. By performing final cold rolling after the solution treatment or after the subsequent sub-zero treatment, it is possible to obtain a desired strength. For this reason, it is preferable to perform final cold rolling at a rolling reduction ratio in the range of 10 to 80% after the solution treatment. If the rolling reduction ratio is less than 10%, sufficient hardness and strength cannot be obtained. For this reason, the final cold rolling reduction ratio is preferably 10% or more.
[0078] On the other hand, if the final cold rolling reduction exceeds 80%, the strength increases too much and the hydrogen embrittlement resistance decreases. For this reason, the final cold rolling reduction is preferably 80% or less. In order to set the hardness in the range of 250 to 450HV1, the final cold rolling reduction is preferably in the range of 20 to 70%. Although the plate-shaped steel plate has been taken as an example and explained, for example, in the case of a rod-shaped or tubular steel material, the reduction in area may be in the range of 10 to 80%. That is, the cold working rate may be adjusted to be in the range of 10 to 80%. In addition, the above range of conditions and other conditions may be adjusted to control the metal structure to be an austenitic stainless steel.
[0079] It is desirable to form a passive film with a high ratio of Cr oxide on the surface after the final cold rolling by removing Fe and Mn oxides as much as possible. This is because the weather resistance is improved as a result. In order to form such a passive film, it is preferable to mechanically polish or electrolytically polish the surface of the steel material. In order to further improve the weather resistance, it is preferable to perform electrolytic polishing. The surface roughness after the above-mentioned polishing is preferably 0.1 μm or less in average roughness Ra.
[0080] Polishing is preferably performed in a range of up to 10 μm from the surface in the direction perpendicular to the plate thickness. Mechanical polishing may be performed using abrasive paper or abrasive stone, or a solid abrasive may be used. In addition, electrolytic polishing may be performed using a commercially available electrolytic polishing solution. The electrolytic polishing process is preferably performed at 40 to 60° C.
[0081] If the electrolytic polishing temperature is less than 40°C, dissolution will not proceed easily, the ratio of Cr oxide in the passive film will be low, and formula (iii) and / or (iv) may not be satisfied. As a result, weather resistance will decrease. For this reason, the electrolytic polishing temperature is preferably 40°C or higher. On the other hand, if the electrolytic polishing temperature exceeds 60°C, excessive Fe oxide will be produced in the passive film, and formula (ii) and / or (iii) may not be satisfied. For this reason, the electrolytic polishing temperature is preferably 60°C or lower. Other conditions include a current density of 1 to 20 dm 2 The time should preferably be within the range of 1 to 10 minutes.
[0082] In order to control the amount of oxide in the passive film to an optimal range and reduce the surface roughness, electrolytic polishing is performed at 40 to 50°C and a current density of 1 to 10 dm 2 The time is preferably in the range of 5 to 10 minutes. After electrolytic polishing, it is preferable to form a passive film by washing with water and drying at 120° C. or less. Specifically, it is preferable to insert the steel material after washing into a drying furnace at 50 to 100° C.
[0083] Through these steps, the austenitic stainless steel material according to this embodiment can be obtained.
[0084] The austenitic stainless steel material according to this embodiment will be described more specifically below with reference to examples, but this embodiment is not limited to these examples. EXAMPLES
[0085] A slab having the composition shown in Table 1 was melted, heated to 1200°C, and then hot-rolled to a thickness of 5.0 mm. The hot-rolled sheet was then annealed and pickled at 1050-1100°C, and cold-rolled to a thickness of 2 mm to obtain a cold-rolled sheet. The cold-rolled sheet was then subjected to a solution treatment in which the sheet was heat-treated at 1050-1100°C for 30 seconds, and then pickled. The obtained steel sheet was subjected to final cold rolling in a range of 10-80% to a thickness of 0.4-1.8 mm. The surface was then finished by mechanical polishing and electrolytic polishing to obtain a test material.
[0086] The mechanical polishing was wet polishing using a grindstone with a grit size of #320. The electrolytic polishing was carried out under different conditions. Electrolytic 1 in Table 2 used the commercially available electrolytic polishing solution S-CLEAN EP at 40 to 50°C and a current density of 3 to 5 dm 2 Electrolytic polishing was performed for 5 minutes at 60°C and a current density of 3 to 5 dm. 2 In electrolysis 3, the same electrolytic polishing solution was used, and the temperature was 30°C, the current density was 3 to 5 dm 2 This shows that electrolytic polishing was performed for 10 minutes. After rinsing with water, the material was placed in a drying furnace at 80°C for 30 minutes. For comparison, a cold-rolled material that was not polished was also evaluated.
[0087] [Table 1]
[0088] The strength, hardness, and crystal structure of each element in the passive film of the obtained test material were examined, and the hydrogen embrittlement resistance was evaluated, according to the following procedures.
[0089] (Strength of each element in the passive film) For the test material, elemental analysis was performed from the surface to the depth direction by GDS to obtain the intensities of O, Fe, Cr, and Mn. The GDS conditions were the above-mentioned pulse sputtering mode with an output of 20 W and a pressure of 600 Pa, and the sputtering depth was 0.1 μm.
[0090] (Hardness measurement) In addition, for the test material, a resin-embedded cross-section sample was prepared, and a load of 1 kg (9.8 N) was applied near t / 2, and a hardness test was performed in accordance with JIS Z 2244: 2020. Specifically, a resin-embedded cross-section sample was prepared, and a load of 1 kg (9.8 N) was applied near t / 2, and a Vickers hardness tester was used to perform a hardness test with the test force held for 20 seconds.
[0091] (Identification of crystal structure) Regarding the crystal structure, X-ray diffraction was performed on the EBSP measurement surface, and the area ratio of fcc structure grains and bcc structure grains was calculated. The conditions for X-ray diffraction were CuKα radiation, an applied voltage of 40 kv, and 2θ in the range of 30°≦2θ≦90°. In the results in Table 2, if the area ratio of bcc was more than 3%, it was marked as "present."
[0092] (Evaluation of hydrogen embrittlement resistance) Hydrogen embrittlement resistance was measured by the following procedure. A tensile test piece with a parallel part of 4 mm width and 20 mm length was taken. The tensile test piece was then immersed in 70 MPa hydrogen and 0.1 MPa nitrogen at -40°C at a strain rate of 10 -5 A slow strain rate tensile test (hereinafter referred to as "SSRT test") was carried out at 10000 / s. The SSRT test was evaluated by measuring the tensile breaking strength and tensile breaking elongation. The hydrogen embrittlement resistance was evaluated using the value calculated by the following formula. Hydrogen embrittlement resistance evaluation value = {(tensile strength or elongation at break in 70 MPa hydrogen) / (tensile strength or elongation at break in 0.1 MPa nitrogen)} × 100 (%) (a)
[0093] When the hydrogen embrittlement resistance evaluation value of the tensile breaking strength calculated from the above formula is 95% or more and the hydrogen embrittlement resistance evaluation value of the tensile breaking elongation is 85% or more, it is deemed to have good hydrogen embrittlement resistance and is marked with "Good". On the other hand, when the hydrogen embrittlement resistance evaluation value is less than the above values, it is deemed to have poor hydrogen embrittlement resistance and is marked with "Poor".
[0094] (weather resistance) Weather resistance was measured using the following procedure. Test pieces measuring 50 mm wide x 100 mm long were taken. The test pieces were then subjected to a combined cycle test (JASO M609) according to the Japan Automotive Engineering Society standard. One cycle consisted of spraying a 5% NaCl aqueous solution (35°C, 2 h), drying (60°C, 4 h), and wetting (50°C, 95% RH, 2 h), and the SARN was measured from the appearance after 30 cycles.
[0095] When the SARN was equivalent to that of SUS304 (18Cr-8Ni), it was deemed to have good weather resistance and was marked with a "Good". Furthermore, when the SARN was higher than that of SUS304, it was deemed to have particularly excellent weather resistance and was marked with a "Excellent". On the other hand, when the SARN was lower than that of SUS304, it was marked with a "Good", and when the SARN was the lowest or lower, it was deemed to have poor weather resistance and was marked with an "X". The results are summarized below in Table 2.
[0096] [Table 2]
[0097] The test materials No. 2 to No. 11, which satisfy the requirements of the chemical composition, A value, and passive film of this embodiment, had the desired hydrogen embrittlement resistance and weather resistance. In particular, No. 3, 4, 6, 8, 10, and No. 11 had the preferred range of strength of Fe, Cr, and Mn oxides in the passive film, and were particularly excellent in weather resistance, rated as ⊚. In addition, No. 3, 8, and No. 10 had a higher ratio of Cr oxide by electrolytic polishing compared to No. 2, 7, and 9, and similarly had particularly excellent weather resistance.
[0098] On the other hand, Nos. 1 and 12 to 19 did not meet any of the requirements of this embodiment for chemical composition, A value, and passive film, and both or either of hydrogen embrittlement resistance and weather resistance were degraded. No. 1 was not polished after cold working and had slightly poor weather resistance, rated △. Nos. 12 to 19 had components and A values outside the specified ranges, and hydrogen embrittlement resistance was degraded. Furthermore, Nos. 20 and 21 had electrolytic polishing conditions outside the preferred ranges, and therefore at least one of formulas (i) to (iii) did not meet the requirements of this embodiment, and weather resistance was degraded. [Industrial Applicability]
[0099] The austenitic stainless steel material according to this embodiment has high strength, hydrogen embrittlement resistance, and weather resistance. Therefore, it is suitable for steel plates, bars, and tubes that are cold worked and used in a high-pressure hydrogen gas environment, and is preferably applied to hydrogen equipment that requires weather resistance in addition to light weight and compactness. The austenitic stainless steel material according to this embodiment contributes to thinning and weight reduction of hydrogen equipment and parts by increasing the strength through cold working and then forming a passivation film. [Explanation of symbols]
[0100] 1. Passive film 2. Base material
Claims
1. An austenitic stainless steel material having a passive film, The chemical composition, in mass%, is C: 0.20% or less, Si: 2.0% or less, Mn: 6.0 to 20.0%, P: 0.060% or less, S: 0.0080% or less, Cr: 10.0-18.0%, Ni: 4.0 to 12.0%, N: 0.01-0.30%, Cu: 4.0% or less, Mo: 3.0% or less, Al: 0-0.20%, Ca: 0-0.01%, B: 0 to 0.01%, Mg: 0 to 0.01%, Nb: 0 to 1.0%, Ti: 0 to 1.0%, V: 0 to 1.0%, W: 0 to 2.0%, Zr: 0 to 1.0%, Co: 0-2.0%, Ga: 0 to 0.10%, Hf: 0-0.10%, REM: 0-0.10%, The balance is Fe and impurities. The A value calculated by the following formula (i) is 30.0 to 60.0, The austenitic stainless steel material, wherein the passive film satisfies the following formulas (ii) to (iv): A value=3.2Mn+0.7Cr+6.2Ni+38.7N+4.8Cu+9.3Mo -53 ... (i) I Fe / I O ≦1.0 ・・・(ii) 0.3<I Cr / - O ≦2.0 ・・・(iii) I Mn / I O <0.3 ・・・(iv) Here, each element symbol in the above formula (i) represents the content (mass%) of each element contained in the steel, and when no element is contained, it is set to zero, and each symbol in the above formulas (ii) to (iv) represents the intensity of each element measured by glow discharge optical emission spectrometry, and is defined as follows: I Fe : Fe intensity (cps) at a depth position where the O intensity is 1 / 2 of the O intensity at the surface I O : O intensity (cps) that is 1 / 2 of the O intensity on the surface I Cr : Cr intensity (cps) at a depth position where the O intensity is 1 / 2 of the O intensity at the surface I Mn : Mn intensity (cps) at a depth position where the O intensity is 1 / 2 of the O intensity at the surface
2. Vickers hardness is 200 to 500 HV1, In the crystal structure, 97% or more of the area ratio is an fcc structure. The austenitic stainless steel material according to claim 1.
3. The chemical composition, in mass%, Al: 0.01-0.20%, Ca: 0.001-0.01%, B: 0.0002-0.01%, Mg: 0.0002-0.01%, Nb: 0.01-1.0%, Ti: 0.01 to 1.0%, V: 0.01-1.0%, W: 0.01-2.0%, Zr: 0.01 to 1.0%, Co: 0.01-2.0%, Ga: 0.01-0.10%, Hf: 0.01 to 0.10%, and REM: 0.01-0.10%, The austenitic stainless steel material according to claim 1 or 2, comprising one or more selected from the following:
4. The austenitic stainless steel material according to any one of claims 1 to 3, which is used in a high-pressure hydrogen gas environment.
5. 5. Hydrogen equipment comprising the austenitic stainless steel material according to claim 1.
6. 6. The hydrogen equipment according to claim 5, wherein the hydrogen equipment is a tank body, a tank cap, a liner, a pipe, a valve, or a heat exchanger.
Citation Information
Patent Citations
Production of austenitic steel excellent in delayed breakage and high toughness
JP1979127830A
AUSTENITIC HIGH-Mn STAINLESS STEEL FOR HIGH-PRESSURE HYDROGEN GAS
JP2007126688A
Austenitic stainless steel material for diffusion bonding and method for manufacturing diffusion-bonded article
JP2013204150A
Method of manufacturing stainless steel member
JP2015227501A
Scrubber and method of manufacturing scrubber
JP2016102427A